2011 IEEE International Symposium on Information Theory Proceedings 2011
DOI: 10.1109/isit.2011.6034162
|View full text |Cite
|
Sign up to set email alerts
|

Interference, cooperation and connectivity — A degrees of freedom perspective

Abstract: THIS PAPER IS ELIGIBLE FOR THE STUDENT PAPER AWARD. We explore the interplay between interference, cooperation and connectivity in heterogeneous wireless interference networks. Specifically, we consider a 4-user locallyconnected interference network with pairwise clustered decoding and show that its degrees of freedom (DoF) are bounded above by 12 5 . Interestingly, when compared to the corresponding fully connected setting which is known to have 8 3 DoF, the locally connected network is only missing interfere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Combining (24) and (25) establishes the desired lemma. The Cognitive MAC is obtained from the original network by revealing the genie-information V 0 , .…”
Section: Then the Multiplexing Gain Of The Network Is Upper Bounded Asmentioning
confidence: 63%
“…Combining (24) and (25) establishes the desired lemma. The Cognitive MAC is obtained from the original network by revealing the genie-information V 0 , .…”
Section: Then the Multiplexing Gain Of The Network Is Upper Bounded Asmentioning
confidence: 63%
“…For simplicity, we use the term CoMP channel to denote the interference channel with CoMP transmission and CoMP reception. In [8], a potential application for studying such a channel is presented. Consider a three-hop wireless network scenario with the interference channel at the center forming a bottleneck.…”
Section: Degrees Of Freedom Of Interference Channels With Comp Transmmentioning
confidence: 99%
“…Special cases of the CoMP channel have been studied in the past under different names such as cognitive interference channel [25]- [29], interference channel with local or partial side information [30], [31], interference channel with clustered decoding [8], or a combination of these terms [32]. However, the DoF of the CoMP channel has not been determined except in some special cases.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies considering the node position distributions and signal attenuation can be found in [27] and [28].…”
Section: Introductionmentioning
confidence: 99%